Pembelajaran Online Berbasis Google Meet Pada Kitab Nikah Karya Syeikh Muhammad Shalih Munjid di Pondok Pesantren Mahasiswa Al-Amin Ronowijayan Ponorogo - Hermawati, Kiki Ayu (Edification Journal : Pendidikan Agama Islam, 2022)
This research has a purpose to analyze: (1) Implementation of online marriage book learning using Google Meet who created by Syeikh Muhammad Shalih Munjid at Islamic Boarding School Al-Amin Ronowiyajan. (2) The advantages and disadvantages online marriage book learning using Google Meet at Islamic Al-Amin Ronowijayan. For this research using approach qualitative with case study. The data obtained for this research trough online interview, online observation, and documentation. While, for data analysis by Miles & Huberman. The findings in this research can be said to be valid because the credibility test has been carried out by extending the research time, persistence of the researcher to obtained data, and triangulation. The findings of the research include: First, learning the book of marriage is carried out every Saturday starting at 04.45 WIB – 05.00 WIB. The female Islam teacher has an important role in controlling learning and can be called teacher centered. Second, the advantages and disadvantages online marriage book learning using Google Meet who created by Syeikh Muhammad Shalih Munjid are: (1) The female Islam teacher and students face to face virtually. (2) Learning can be controlled by the female Islam teacher because all cameras are alive. While the advantages are: (1) the students have badly signal. (2) Learning with Google Meet consumes up internet quota.